Psychological Capital and Work Engagement in Employees at PT. BMU Balikpapan - Veren Varonicha Ambarwati; Sutarto Wijono (International Journal Labs, 2023)
At its core, work engagement signifies a state in which employees exhibit their utmost performance driven by a genuine enjoyment of their tasks. Concurrently, psychological capital denotes an individual's psychological state characterized by a positive self-perception, facilitating optimal functioning. The focal point of this research lies in unraveling the interplay between psychological capital and work engagement within the workforce of PT. BMU Balikpapan. The study incorporates a quantitative approach with a sample size comprising 35 male and female employees. Employing two scales—psychological capital and work engagement—the research yields noteworthy results. The data analysis, with a significance value of 0.000 (P<0.05), unequivocally asserts a substantial positive correlation between psychological capital and work engagement among employees at PT. BMU Balikpapan. In essence, this implies that individuals possessing a heightened psychological capital are more likely to exhibit elevated levels of work engagement. The contribution of this relationship's efficacy is quantified at 8.7%, emphasizing the considerable impact of psychological well-being on the overall engagement of the workforce. These findings carry implications for organizational strategies aimed at optimizing employee performance and satisfaction. Recognizing the pivotal role of psychological capital in fostering work engagement, PT. BMU Balikpapan and similar entities are encouraged to integrate initiatives that nurture positive self-perceptions among employees, ultimately contributing to a more productive and fulfilling work environment.